2015
DOI: 10.1038/srep12911
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-29 has a significant lipid-lowering benefit through suppression of lipogenic programs in liver

Abstract: MicroRNAs (miRNAs) are important regulators and potential therapeutic targets of metabolic disease. In this study we show by in vivo administration of locked nucleic acid (LNA) inhibitors that suppression of endogenous miR-29 lowers plasma cholesterol levels by ~40%, commensurate with the effect of statins, and reduces fatty acid content in the liver by ~20%. Whole transcriptome sequencing of the liver reveals 883 genes dysregulated (612 down, 271 up) by inhibition of miR-29. The set of 612 down-regulated gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 56 publications
9
65
0
Order By: Relevance
“…Indeed, here, we identified miR-29a/b/c to be affected by Dicer1-deficiency; thus, their inhibitory effect on HMGCR mRNA and protein expression (Figure 4) was diminished by Dicer1 knockout. Specifically, we have revealed that miR29a/b/c are employing their inhibitory effects by acting via their seed region to form hybrids with the 3'-UTR of HMGCR mRNA, which is in agreement with a recently published report [49] . Excess cholesterol and 25-hydroxycholesterol decreased HMGCR expression in vitro ( Figure 5), which may be due to the increased miR-29a levels, suggesting that in normal conditions, the cells induced miR-29a expression to reduce HMGCR expression and to balance cellular cholesterol levels.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, here, we identified miR-29a/b/c to be affected by Dicer1-deficiency; thus, their inhibitory effect on HMGCR mRNA and protein expression (Figure 4) was diminished by Dicer1 knockout. Specifically, we have revealed that miR29a/b/c are employing their inhibitory effects by acting via their seed region to form hybrids with the 3'-UTR of HMGCR mRNA, which is in agreement with a recently published report [49] . Excess cholesterol and 25-hydroxycholesterol decreased HMGCR expression in vitro ( Figure 5), which may be due to the increased miR-29a levels, suggesting that in normal conditions, the cells induced miR-29a expression to reduce HMGCR expression and to balance cellular cholesterol levels.…”
Section: Discussionsupporting
confidence: 79%
“…The inhibition of miR29a also slightly increased the hepatic cholesterol level [49,52] . However, when mice were fed with a high-fat diet (HFD) for 16 weeks, the inhibition of miR-29a caused a 2-fold FC accumulation in the liver of mice, more obvious than the accumulation of TG [52] .…”
Section: Discussionmentioning
confidence: 96%
“…13). In support of this prediction, a recent study reported that the 3'-UTR of human AhR was directly recognized by miR-29a in Huh-7 cells (Kurtz et al, 2015), although a functional MRE for miR-29a has not been experimentally identified. miR-29 family members, including miR-29a, are known to be down-regulated in human fibrotic livers (Roderburg et al, 2011).…”
Section: Discussionmentioning
confidence: 62%
“…There is also evidence suggesting that CYP enzymes might be regulated by miRNA through AHR pathways (Table 3). For instance, in vivo administration of locked nucleic acid-modified antisense miR-29 antagomir to mice altered the expression of many hepatic proteins, including the upregulation of Ahr, Cyp1a1, Cyp2b10, Cyp3a11, and Cyp4a12 (Kurtz et al, 2015). A conserved miR-29 MRE site within the 39UTR of human AHR and mouse Ahr was then validated by luciferase reporter assay, demonstrating that AHR is a direct target of miR-29.…”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 99%